POTENSI PENALARAN FORMAL MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL CERITA KONTEKSTUAL - Deni, Deni; Sugiatno, Sugiatno; BS, Dian Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to describe the potential of formal mathematical reasoning of students in solving contextual story problems in terms of their mathematical ability level on Linear Equation System Material Two Variables and Three Variables In Class XII IPA Madrasah Aliyah Khulafaur Rasyidin Kubu Raya academic year 2017/2018. The research method used is descriptive with case study research. The chosen subjects were 20 students that divide be three group, then chosen three students of the group. The result of data analysis shows that students' formal reasoning ability is in accordance with their mathematical ability. That is, the students' formal math reasoning ability in solving contextual story that belongs to the upper group is included in the high category (46.67%), the students belonging to the middle group are included in the medium category (30%), and the students belonging to the lower group including in the low category (20%).Â Keywords: Ability, Potential, Formal Mathematical Reasoning